The politicization of intellectual property rights in the context of Karabakh - Adalat Jalal Muradov; Nargiz Hajiyeva (Cogent Social Sciences, 2024)
Until recently, intellectual property law has been kept away from the political realm, as it was merely linked to economic and legal factors. However, in light of recent geopolitical processes and politically charged conflicts, political science has taken dominance in terms of intellectual property (IP) development and proclivities. In contemporary international politics, it is critical to explain and perceive IP tendencies and systems from the perspectives of political science and political economy, to consider appropriate retorts to processes arising from IPR conflicts in the Karabakh region of Azerbaijan during the occupation. Azerbaijan had been confronted with limitations of its control over its territory due to the nearly three decades of the Karabakh conflict. In this regard, the article will answer questions related to the violation of intellectual property rights in the Karabakh region, the exploitation of goods and services, and the IPR problems encountered by Azerbaijan during the occupation of Karabakh.